Bone marrow transplantation only partially restores purine metabolites to normal in adenosine deaminase-deficient patients. - Hirschhorn, R (1981)
To delineate the extent to which bone marrow transplantation provides "enzyme replacement therapy", we have determined metabolite concentrations in two patients with adenosine deaminase (ADA) deficiency treated with bone marrow transplants and rendered immunologically normal. 10 yr after engraftment of lymphoid cells, erythrocyte deoxy ATP was markedly decreased compared to the marked elevations of deoxy ATP observed in untreated patients, but was still significantly elevated (62 and 90 vs. normal of 6.0 +/- 6.0 nmol/ml packed erythrocytes). Similarly, deoxyadenosine and adenosine excretion were both markedly diminished compared to that of untreated patients but deoxyadenosine excretion was still clearly increased (20.1 and 38.6 vs. normal of less than 0.2 nmol/mg creatinine) while adenosine excretion was in the upper range of normal (7.0 and 8.1 vs. normal of 5.6 +/- 3.6 nmol/mg creatinine). Mononuclear cell deoxy ATP content was also elevated compared to normal (5.25 and 14.4 vs. 1.2 +/- 0.3). Separated mononuclear cells of bone marrow transplanted patients contain both donor lymphocytes and recipient monocytes. When mononuclear cells were depleted of the cells enriched for donor lymphocytes (i.e. monocyte depleted) was lower than that of the mixed mononuclear cells (2.2 vs. 5.26). Surprisingly, plasma adenosine was as high as in untreated ADA-deficient patients (3.2 and 1.5 vs. untreated of 0.3-3 microM). Consistent with the elevated plasma adenosine and urinary deoxyadenosine, erythrocyte S-adenosyl homocysteine hydrolase activity was diminished (0.88 and 1.02 vs. normal of 5.64 +/- 0.25). Thus, bone marrow transplantation of ADA-deficient patients not only provides lymphoid stem cells, but also partially, albeit incompletely, clears abnormally increased metabolites from nonlymphoid body compartments.